2018
DOI: 10.3126/nvj.v35i0.25247
|View full text |Cite
|
Sign up to set email alerts
|

Serodiagnosis of Toxoplasmosis using Lateral Flow Chromatographic Immunoassay among Animals and Humans in Sunsari District of Nepal

Abstract: Toxoplasmosis is a cosmopolitan parasitic zoonosis, infecting human and other warm-blooded animals worldwide. This disease has economic importance in regard to animal reproduction, and it leads to abortions and neonatal complications in humans. This study was carried out to determine the seroprevalence of Toxoplasma gondii in sheep, cattle, cats and human in Inaruwa and surrounding areas of Sunsari district, Nepal. Altogether 336 blood samples, of which 50 from sheep, 92 from cattle, 44 from cats and 150 from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…16 out of 44 were positive for toxoplasmosis. Also, the same study showed that the occurrence of human toxoplasmosis was more among the farmers followed by butcher, and most of the positive human had contact with cats (Sah et al, 2018).…”
Section: Toxoplasmosismentioning
confidence: 80%
“…16 out of 44 were positive for toxoplasmosis. Also, the same study showed that the occurrence of human toxoplasmosis was more among the farmers followed by butcher, and most of the positive human had contact with cats (Sah et al, 2018).…”
Section: Toxoplasmosismentioning
confidence: 80%